Tenosynovial Giant Cell Tumor of Foot in a Patient with Radioiodine-Refractory Thyroid Cancer: Imaging Findings on FDG-PET/CT, MRI, and Radioiodine Scan - Loharkar, Sarvesh; Basu, Sandip (World Journal of Nuclear Medicine, 2022)
We herein illustrate a case of benign tenosynovial giant cell tumor, which was incidentally detected as FDG-avid lesion on PET/CT in a patient with radioiodine refractory thyroid cancer, with predominantly non-iodine concentrating disease. The lesion was followed up clinically and with local MRI annually for subsequent 3 years. The utility of hybrid PET-CT imaging, the non-iodine concentration of the tumor along with clinical knowledge, and findings on other imaging and pathological modalities in answering and diagnosing incidental benign musculoskeletal tumors in a patient with known thyroid malignancy are presented here.
Keywords: benign tenosynovial giant cell tumor; 18F-FDG-PET/CT; benign bone tumor; radioiodine refractory thyroid cancer; thyroglobulin elevated negative iodine scintigraphy; differentiated thyroid carcinoma